Trend of Patients' Compliance in a Public Hospital Before and After Healthcare Reform Implementation - Ahmad Sadeghi; hossein Rohani; Sareh Davarzani; Zahra Davarzani (Tehran University of Medical Sciences, 2018)
Background: Patient complaints from the healthcare system can be helpful to respond patients' needs using identifying the weaknesses. In this study, the complaints trend of patients has been investigated before and after healthcare system reform progress in a public hospital.   Materials and Methods: This descriptive-analytic study was carried out to assess trend of patientchr('39')s complaints in two period of time in a northeast governmental hospital before and after healthcare system reform implementation (2012-2016). In order to collect data, the checklist designed by the ministry of Health was used. Data entered to SPSS version 21 and analyzed using descriptive statistics and analytical tests such as Chi-square.   Results: The study results revealed that the number of complaints were 29 and 198 before and after implementation of healthcare system reform, respectively. Most complaints were related to the emergency sector (31%) and about 40% of the complaints were from physicians. Most of the registered complaints were related to the quality of provided services (33.5%) and personnel exposure (30%), respectively. Accordance to study results, there was a significant difference between the number of complaints before and after implementation of the health system reform with the type of complainant (P <0.05).   Conclusion: Implementation of healthcare reform plan has led to systematic registration and special attention to complaints in assessed hospital. Most of registered complaints were related to the emergency department which requires managers and hospital officials to pay special attention to this sector and take effective steps to improve quality of services.